PENGARUH VARIASI LETAK SIRIP BERONGGA PADA ALAT DISTILASI SURYA TERHADAP HASIL AIR TAWAR - Mirmanto, M.; Sayoga, I Made Adi; Guna, Patar Dayu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Mataram, 2022)
For humans, clean water is a basic need in life. All life activities require water such as for bathing, cooking, washing and drinking. As time goes by and the world's population increases, the supply of clean water is decreasing. Some areas in the southern coast of Java, West Nusa Tenggara and East Nusa Tenggara often experience difficulties in obtaining clean water which is repeated every dry season arrives. The purpose of this study was to determine the effect of variations in the location of the hollow fins on the amount of fresh water produced. The data generated is the quantity of fresh water, the intensity of the sun, the speed of the wind around the distillation apparatus, the temperature of the water in the distillation apparatus. Varied are absorbers with flat plates, sleeping fins and standing fins. The research results show that standing fin absorbers produce the fresh water. On the first day, the mass of fresh water was 1.092 kg. On the second day, the fresh water obtained was 1.045 kg and on the third day, the fresh water obtained was 0.798 kg.